Pengaruh kualitas akustik pada produktivitas kerja dan tingkat psychosocial stress di ruang basement - Maria Christina Prasetya; Frengky Benediktus Ola (ARTEKS : Jurnal Teknik Arsitektur, 2022)
The basement lobby area in Campus II of Universitas Atma Jaya Yogyakarta was originally designed to function as a vehicle parking and laboratory space with noise-generating equipment, but it is currently being used as a place for students to do assignments. Meanwhile, it has been discovered that psychosocial stress can be caused by continuous exposure to noise, thereby, making it necessary to consider the quality factor of the indoor environment of this area for students use. Therefore, this study was conducted to determine the effect of the noise in the basement lobby area on student work productivity and psychosocial stress. This involved the use of a quantitative method by measuring the noise level using Phonic PAA3 per one point in the 4 segments of the corridor according to the provisions of SNI 7231:2009. Moreover, a qualitative approach was also applied by distributing online and offline questionnaires to determine the perception of noise, psychosocial stress, and its effect on work productivity. A total of 109 respondents consisting of 48 architecture, 40 civil engineering, and 21 techno-biology students using the lobby as a place to do assignments were used as the respondents. The data obtained were analyzed using a simple regression method in the SPSS25 program. It is important to note that the quantitative and qualitative measurements were not conducted simultaneously. The results showed that the study room does not fulfill the standard reference value of 45dB required for the noise level as indicated by the highest and lowest noise (Leq) values recorded to be 74.10dB and 64.34dB in segments B and A, respectively, as well as the overall average of 70.1dB. Furthermore, the combination of the qualitative and quantitative data showed that the noise affects students' psychosocial stress by 43% and productivity by 45%, hence, this means the noise reduced the student productivity. Therefore, the noise factor needs to be considered in planning a workspace or converting the function of space in order to ensure its purpose is achieved maximally.